COOPERATION BETWEEN UZBEKISTAN AND TAJIKISTAN DURING THE YEARS OF INDEPENDENCE - Nomozov Shokhrukh Azamat ogli (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article describes the establishment of diplomatic relations with Tajikistan during the years of Uzbekistan’s independence, political meetings, treaties, and agreements between the two countries to this day.